Enhanced Transgene Expression by Optimization of Poly A in Transfected CHO Cells - Wang, Xiao-yin; Du, Qiu-jie; Zhang, Wei-li; Xu, Dan-hua; Zhang, Xi; Jia, Yan-long; Wang, Tian-yun (Frontiers in Bioengineering and Biotechnology, 2022)
The generation of the stable, high-level recombinant protein-producing cell lines remains a significant challenge in the biopharmaceutical industry. Expression vector optimization is an effective strategy to increase transgene expression levels and stability, and the choice of suitable poly A element is crucial for the expression of recombinant protein. In this study, we investigated the effects of different poly A elements on transgene expression in Chinese hamster ovary (CHO) cells. Five poly A elements, including bovine growth hormone (BGH), mutant BGH, herpes simplex virus type 1 thymidine kinase (HSV-TK), SV40, and a synthetic (Synt) poly A, were cloned into the expression vector and transfected into CHO cells. The results indicated the SV40 and Synt poly A sequences can significant improve eGFP transgene expression in stable transfected CHO cells and maintain long-term expression. However, qPCR results showed that the eGFP expression at protein level was not related to the gene copy number and mRNA level. Importantly, the SV40 and Synt poly A elements decreased the variation of eGFP transgene expression. Furthermore, it also showed that the SV40 and Synt poly A elements induced higher levels of adalimumab expression. In conclusion, SV40 poly A and Synt poly A are stronger elements that increase stable transgene expression and decrease the variation of expression, and the choice of suitable poly A element is helpful to improve the expression of recombinant protein.